Leptospira ainlahdjerensis sp. nov., Leptospira ainazelensis sp. nov., Leptospira abararensis sp. nov. and Leptospira chreensis sp. nov., four new species isolated from water sources in Algeria. Issue 12 (16th December 2021) - Korba, Anissa Amara; Lounici, Hakim; Kainiu, Malia; Vincent, Antony T.; Mariet, Jean-François; Veyrier, Fréderic J.; Goarant, Cyrille; Picardeau, Mathieu
Abstract : Leptospira strains were isolated from freshwater sampled at four sites in Algeria and characterized by whole-genome sequencing and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). The cells were spiral-shaped and motile. Phylogenetic and MALDI-TOF MS analyses showed that the strains can be clearly distinguished from the other described species in the genus Leptospir a, therefore representing two novel species of the pathogen subclade P1 and two novel species of the saprophyte subclade S1. The names Leptospira ainlahdjerensis sp. nov. (type strain 201903070 T =KIT0297 T =CIP111912 T ), Leptospira ainazelensis sp. nov. (201903071 T =KIT0298 T =CIP111913 T ), Leptospira abararensis sp. nov. (201903074 T =KIT0299 T =CIP111914 T ) and Leptospira chreensis (201903075 T =KIT0300 T =CIP111915 T ) are proposed.